Solitary Rectal Ulcer Syndrome: An Unusual Cause of Per Rectal Bleeding in Children (Journal of Enam Medical College, 2023)
Solitary rectal ulcer syndrome (SRUS) is a relatively uncommon but troublesome chronic benign disorder more in young adults and less in children. It is usually presented as rectal bleeding, constipation, copious mucous discharge, prolonged excessive straining, tenesmus, lower abdominal pain, localized pain in the perineal area, feeling of incomplete defecation and rarely rectal prolapse.The underlying etiology is not well known. It is diagnosed based on symptoms and endoscopic and histological findings.J Enam Med Col 2021; 11(1): 47-51